2014
DOI: 10.1002/macp.201400226
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Distortion Surface Functionalization of Polymeric Microstructures

Abstract: Polymeric microstructures can be immersed in an organic solution containing a reactive linker to functionalize the surface for attachment of nanoparticles, fluorescent dyes, proteins, DNA, and other species. However, organic media can swell and distort polymeric microstructures. Swelling and distortion can be irreversible when the linkers are themselves low‐molecular‐weight organics like ethylenediamine, which can bind to unreacted monomer groups or other functionalities within the polymer matrix. This work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…This metallization method is not limited to silver plating but is also feasible in the case of other metals. Later, selective copper coating onto SU-8 microstructures was achieved in a similar fashion, [88,105] demonstrating the universal nature of this approach.…”
Section: Nonselective/selective Metal Coatingmentioning
confidence: 95%
“…This metallization method is not limited to silver plating but is also feasible in the case of other metals. Later, selective copper coating onto SU-8 microstructures was achieved in a similar fashion, [88,105] demonstrating the universal nature of this approach.…”
Section: Nonselective/selective Metal Coatingmentioning
confidence: 95%
“…For example, acrylic polymers swell when immersed in polar solvents like alcohols and much less in water. Although polymerized SU-8 can swell in water due to the hydroxyl groups formed upon polymerization, the dimensional variation is typically minimal and saturates in minutes [ 82 , 83 ]. This makes SU-8 an ideal material for microfluidic application where aqueous solutions are typically used.…”
Section: Su-8 Devices Fabricated By Multi-photon Lithographymentioning
confidence: 99%
“…Amination can be carried out by simply immersing the SU-8 surface in a solution of an alkyl diamine (e.g., ethylenediamine) in ethanol. Kuebler et al reported that this procedure causes irreversible shrinkage and distortion in SU-8 micro-lattices fabricated by MPL because as the ethanol solution of ethylenediamine infuses and swells the structure, it can react with unpolymerized oligomers and wash them away, causing irreversible distortion ( Figure 13 b) [ 83 ]. To remedy this problem, the authors investigated aqueous amination solutions which resulted in much lower irreversible distortion upon amination ( Figure 13 c) [ 83 ].…”
Section: Metallization Of Su-8 Micro-structuresmentioning
confidence: 99%
See 2 more Smart Citations